Clinical geneticists' views of VACTERL/VATER association - Benjamin D. Solomon; Kelly Bear; Virginia Kimonis; Annelies de Klein; Daryl A. Scott; Charles Shaw‐Smith; Dick Tibboel; Heiko Reutter; Philip F. Giampietro (2012)
Abstract VACTERL association (sometimes termed “VATER association” depending on which component features are included) is typically defined by the presence of at least three of the following congenital malformations, which tend to statistically co‐occur in affected individuals: Vertebral anomalies, Anal atresia, Cardiac malformations, Tracheo‐Esophageal fistula, Renal anomalies, and Limb abnormalities. Although the clinical criteria for VACTERL association may appear to be straightforward, there is wide variability in the way clinical geneticists define the disorder and the genetic testing strategy they use when confronted with an affected patient. In order to describe this variability and determine the most commonly used definitions and testing modalities, we present the results of survey responses by 121 clinical geneticists. We discuss the results of the survey responses, provide a literature review and commentary from a group of physicians who are currently involved in clinical and laboratory‐based research on VACTERL association, and offer an algorithm for genetic testing in patients with this association. © 2012 Wiley Periodicals, Inc.